Microplastics contamination in commercial fish from Alexandria City, the Mediterranean Coast of Egypt. (15th November 2022) - El-Sayed, Abeer A.M.; Ibrahim, Mohamed I.A.; Shabaka, Soha; Ghobashy, Mohamed M.; Shreadah, Mohamed A.; Abdel Ghani, Safaa A.
Abstract: Plastic waste is a major threat to various marine ecosystems. Due to being semi-enclosed basin with dense population, the Mediterranean Sea has been considered as a hot spot for plastic pollution. Alexandria was listed as one of the major cities contributing to plastic waste in the eastern Mediterranean basin. Accordingly, microplastics (MPs) abundance and composition were investigated in the digestive tracts of commercial fish species from two major fishing areas in Alexandria; Abu-Qir Bay and Eastern Harbor, which are affected by plastic pollution. The incidence and average densities of MPs were 91.8 ± 8.4% and 11.7 ± 9.5 items fish −1, similar to highly polluted regions in the southeastern Mediterranean Sea. The average MPs concentration was significantly higher in Sparus aurata (38.3 ± 28.4 items fish −1 ) than all species, except for Siganus rivulatus and Boops boops . Polyethylene and poly ethylene-vinyl acetate were the dominant polymers in the fish digestive tracts. Four types of plastic polymers were recorded in Siganus rivulatus and five in Parupeneus macronemus . The dominance of glossy fragments (sizes <500 μm) in Abu-Qir Bay indicated land-based source of pollution from domestic, agricultural, and industrial wastes. The dominance of larger plastic filaments and colored fragments in the Eastern Harbor suggested secondary MPs, originating from the fragmentation of larger plastic items of sea-based sources, such as fishing and recreational activities. Graphical abstract: Image 1 Highlights: Microplastics were found in 92% of fish species from Alexandria city, Egypt. Filaments and glossy fragments were the most common shapes of microplastics. Polyethylene and poly(ethylene-vinyl acetate) were the dominant plastic polymers. Sparus aurata had the highest level of microplastics (∼38.3 ± 28.4 items fish −1 ). Land- and sea-based activities were sources of plastics in the Bay and Harbor.